2001
DOI: 10.1107/s0907444901017735
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and preliminary X-ray diffraction studies of catalase–peroxidase fromSynechococcusPCC 7942

Abstract: The recombinant catalase–peroxidase of Synechococcus PCC 7942 overexpressed in Escherichia coli was purified and crystallized by the hanging‐drop vapour‐diffusion method using sodium formate as a precipitant. The crystals belonged to the tetragonal space group P41212 or P43212, with unit‐cell parameters a = b = 109.3, c = 202.0 Å. The calculated VM value based on a dimer in the asymmetric unit was 1.9 Å3 Da−1. A native data set was collected to 2.3 Å resolution from a frozen crystal using synchrotron radiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 12 publications
(14 reference statements)
1
55
0
Order By: Relevance
“…Attempts to crystallize HPI from E. coli had commenced unsuccessfully in 1987, and success with the M. tuberculosis enzyme was no better. Persistence was finally rewarded in 2001 and 2002 with preliminary reports of the crystallization of catalase-peroxidases from the halophilic archaebacterium Haloarcula marismortui [48], from the cyanobacterium Synechococcus [49] and the Gram-negative bacterium Burkholderia pseudomallei [50], and of the C-terminal domain of HPI of E. coli [51]. The structure of the H. marismortui enzyme (HmCPx) at 2.0 Å was reported first [52], followed by the structure of the B. pseudomallei enzyme (BpKatG) at 1.7 Å [53].…”
Section: Catalase-peroxidase Structuresmentioning
confidence: 99%
“…Attempts to crystallize HPI from E. coli had commenced unsuccessfully in 1987, and success with the M. tuberculosis enzyme was no better. Persistence was finally rewarded in 2001 and 2002 with preliminary reports of the crystallization of catalase-peroxidases from the halophilic archaebacterium Haloarcula marismortui [48], from the cyanobacterium Synechococcus [49] and the Gram-negative bacterium Burkholderia pseudomallei [50], and of the C-terminal domain of HPI of E. coli [51]. The structure of the H. marismortui enzyme (HmCPx) at 2.0 Å was reported first [52], followed by the structure of the B. pseudomallei enzyme (BpKatG) at 1.7 Å [53].…”
Section: Catalase-peroxidase Structuresmentioning
confidence: 99%
“…Today the crystal structures of four bacterial CPs have been defined (see Protein Data Bank at RCSB for details, Wada et al, 2002;Bertrand et al, 2004). Structural analysis revealed that the proximal and distal heme pockets in the N-terminal domains contain conserved amino acids at almost identical positions as in the other class I peroxidases APx and CcP.…”
Section: Introductionmentioning
confidence: 99%
“…The crystal structures of KatG from four different organisms, including Haloarcula morismortui (23,24), Synechococcus PCC7492 (25), Burkholderia pseudomallei (BpKatG) (26,27), and M. tuberculosis (28), along with the structures of the predominant INH-resistant variant S315T of MtKatG (7) and its homologue in BpKatG, S324T (22) 426 , is essential for catalase activity, but not peroxidase activity. These structures have provided many insights into KatG structure and function and confirmed the considerable similarity in structure between BpKatG and MtKatG consistent with the similarity in enzymatic properties (16).…”
Section: Isonicotinic Acid Hydrazide (Isoniazid or Inh)mentioning
confidence: 99%